1983
DOI: 10.1002/eji.1830130310
|View full text |Cite
|
Sign up to set email alerts
|

Detection of interspecies idiotypic cross‐reactions associated with antibodies to hepatitis B surface antigen

Abstract: A common idiotype was defined by a rabbit anti-idiotypic antiserum generated against human antibodies to hepatitis B surface antigen (anti-HBs). This idiotype was detected in anti-HBs from eight different individuals who had been previously infected with hepatitis B virus and is referred to as the CHBs idiotype. The CHBs idiotype was also identified in sera from rabbits, mice, guinea pigs, swine, goats and chimpanzees that had been immunized with hepatitis B surface antigen (HBsAg). Expression of the CHBs idio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…The potential usefulness of anti-id for antigenspecific immunosuppression is limited by the need to produce specific, anti-id antisera for each patient. Our results demonstrating crossreactivity remove this limitation, and are in concordance with findings in such diverse antigen systems as Hepatitis B (42), rheumatoid factor (43), p-azophenylarsonate (44), and more recent studies with acetylcholine receptor (45). The findings of crossreactivity and an anti-id that conformationally appears to be the "internal image" of antigen places this anti-id in the second class of a recently proposed system for categorizing anti-ids (46,47), and implies a common, antigenic determinant for the Rbabs binding site.…”
Section: Discussionsupporting
confidence: 90%
“…The potential usefulness of anti-id for antigenspecific immunosuppression is limited by the need to produce specific, anti-id antisera for each patient. Our results demonstrating crossreactivity remove this limitation, and are in concordance with findings in such diverse antigen systems as Hepatitis B (42), rheumatoid factor (43), p-azophenylarsonate (44), and more recent studies with acetylcholine receptor (45). The findings of crossreactivity and an anti-id that conformationally appears to be the "internal image" of antigen places this anti-id in the second class of a recently proposed system for categorizing anti-ids (46,47), and implies a common, antigenic determinant for the Rbabs binding site.…”
Section: Discussionsupporting
confidence: 90%
“…For example, four rabbit antisera raised against two different human IgG anti-hepatitis B virus surface antigen (HBs) preparations detected a common determinant shared by three anti-HBs preparations, and anti-HBs-positive sera obtained from six haemophiliac patients. This anti-HBs idiotype was not found on IgG isolated from sera negative for anti-HBs (Kennedy & Dreesman, 1983). Similar data have been reported in other cross-reactive idiotypic systems (Zouali et al, 1984a, b).…”
Section: Discussionsupporting
confidence: 89%
“…Whereas the human immune response to HBs is idiotypically restricted (Kennedy & Dreesman, 1983), we found that anti-gpl20 antibodies of HIV-l-infected individuals express unrelated idiotypic determinants. These idiotypic features of the humoral immune responses against the hepatitis B virus (HBV) and HIV, which are associated with 'natural' infection of man, may reflect the genomic heterogeneity of HBV and HIV.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, idiotypic sharing has been found among antibodies raised in goats to human hemoglobins (13), and human antibodies to hepatitis B surface antigen ( 14). Similarly, autoantibodies to rheumatoid factors (15), anti-acetylcholine receptor (16) antibodies, antithyroglobulin antibodies (17), and DNA antibodies (7) have all been shown to share idiotypic determinants: These observations indicate restrictions in the repertoire of variable region immunoglobulin genes, and imply that major cross-reactive idiotypic families are the products of common germ line genes dispersed throughout the population rather than the result of somatic mutations.…”
Section: Discussionmentioning
confidence: 99%